Decision-Making System for Selection of Majors in Higher Education Using the Certainty Factor (CF) Method for Web-Based High School Students - Sumito, Robi (Lembaga KITA, 2021)
Various information about college majors has been widely available in print media and on the internet so as to make it easier to get that information. However, the information provided only provides a general description, such as profile, costs, location, and other general information. This information has not fully helped provide input on majors that match the abilities, interests, and preferences of prospective students. the objectives of this research are; to determine the Decision-Making System for Selection of Departments in Higher Education Using the Certainty Factor (CF) Method for Web-Based High School Students, and design a prototype of the Decision-Making System for Selection of Departments in Higher Education Using the Certainty Factor (CF) Method which runs on various operating systems. Based on the results of research and testing on the design of the Decision-Making System for the Selection of Departments in Higher Education using the Certainty Factor (CF) Method for Web-based High School Students that has been carried out by the author, several conclusions can be drawn, namely; This study succeeded in making an expert system design for the selection of majors in higher education for high school students using the Certainty Factor (CF) method and this study succeeded in analyzing the results of the IF THEN ELSE calculation using Certainty Factor (CF).